if you sailed on the mayflower in 1620 - McGovern, Ann (New York : Scholastic Inc, 1969)
Questions and answers describe the voyage of the Mayflower and the Pilgrim's first year in the New World.
G4
Keywords: Mayflower (Ship) -- Juvenile literature; Pilgrims (New Plymouth Colony) -- Juvenile literature